PENGARUH EPS ROA DAN ROE TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA PERIODE 2017 – 2021 - Reken, I Gusti Nyoman; Adiandari, Ade Maharini (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
The capital market is like a place where people can buy and sell something called securities, namely bonds and stocks. Understanding how much a stock is worth is very important for investors who want to invest their money. The value of a stock is determined by how many people want to buy it and how many people want to sell it. The stock price shows how much the value of a company is, and if the company's performance is good, many people want to buy its shares. The purpose of the study is to see how certain things affect the share price of mining companies in Indonesia. This study looks at factors such as EPS, ROA and ROE of companies from 2017 to 2021. By studying 42 mining companies and collecting information from 39 of these companies whose data is taken from the IDX (Indonesian Stock Exchange). Uses several statistical techniques to analyze the data. The results of the study show that EPS and ROA all have a significant and positive effect on stock prices. However, ROE has a significant and negative impact on stock prices.